The mysterious image - Keene, Carolyn; Frame, Paul 1913- (New York Wanderer Books, 1984)
Nancy sets out to locate a kidnapped actress and to clear one of her father's clients, a renowned photographer, accused of stealing ideas for his images.
Keywords: Mystery and detective stories